Análisis fenológico en pastizales de dehesa (Pastos, 1980)
One oí the features of the dynamics of the grazing-lands is represented by its evolution during primary growth, when all phenological sings of the plants are seen. In the «dehesa» área in Salamanca, the prevernal, vernal and aestival periods are the most significant, and show the highest quantity of differentiatingpoints between one typegrazing-land and another. It was during these periods that regular observadons were made in 21 allotments, which belong to the most representative communities in the área, showing for each of the species its phenological state at any given moment. The information gathered has been simplified so as to offer a more general view of the phenological aspects of each type of grazing-land, summarizing the observations made per species for the group of pastures of similar taxonomic category. Likewise, the species which showed phisionomical character were selected, i.e.: those which contribute in highest proportion to the biomass of the community; in a word, those species which are dominant due to their hi^her absolute frecuency or their greater covering. To-complement this, the characteristic species are also considered. This study, descriptive in its essence, enables us on the one hand, to correlate the specific phenological observations with the general characteristics of the grazing-land to which they belong, and, in the other, to analyse the evolution of the same species in different pastures. The results obtained are given graphically, showing the differences between the definable types of pasture using the oligotrophy-eutrophy gradient